Prophetic Transformational Leadership: Enhancing Madrasah Quality and Organizational Culture through Islamic Values - Eka Hashifa An Zhahra; Richway; Hafizul Husni (Sustainable, 2024)
This study examines the integration of prophetic leadership values with transformational leadership and its impact on organizational culture and madrasah quality improvement. Using a qualitative library research design, this study analyzed 22 peer-reviewed articles published between 2019-2024 retrieved from Google Scholar. The findings reveal that integrating five prophetic dimensions (siddiq, amanah, tabligh, fathonah, and rahmah) with transformational leadership components creates a culturally authentic framework that transforms hierarchical madrasah cultures into collaborative, spiritually grounded learning communities. This integration operates through three levels: conceptual alignment, practical application, and outcome enhancement, producing superior results compared to conventional transformational leadership alone. The synthesized evidence demonstrates significant improvements across multiple quality dimensions, including academic achievement, character development, organizational effectiveness, and community satisfaction. The study concludes that prophetic-transformational leadership provides a holistic approach that balances academic excellence with spiritual authenticity in Islamic educational settings. These findings offer practical implications for madrasah principals and policymakers in developing leadership competencies and revising accreditation standards to incorporate prophetic values.